QRIS ShopeePay User Loyalty: The Role of Customer Satisfaction in Mediating Service Features and Brand Image - Nadia, Fitria Ilma; Firmansyah, Fani (Manunggal Halim Jaya, 2025)
Integrating technology into service features and branding strategies is key to maintaining customer loyalty and satisfaction in the digital era. This study aims to analyze the influence of service features and brand image on customer loyalty, mediated by customer satisfaction among Gen Z users of QRIS services in Malang City. Using a quantitative approach with a cross-sectional method, data collection was conducted through a survey of 112 respondents selected using purposive sampling. This study employs Partial Least Squares (PLS) 3.0 analysis to examine the relationships between variables. The findings indicate that service features positively and significantly affect customer loyalty. However, brand image does not have a substantial direct impact on customer loyalty. Both service features and brand image positively and significantly influence customer satisfaction. Furthermore, customer satisfaction significantly mediates the relationship between service features, brand image, and customer loyalty.